Kentucky Derby - Wiseman, Blaine (Sporting championships, 2011)
"Every year, spectators flock to Louisville, Kentucky, to watch one of the world's best-known horse races. Known as 'the most exciting two minutes in sports,' the Kentucky Derby features fast horses, skilled jockeys, and intense competition."--Back cover.